PHOTOCATALYTIC DEGRADATION EFFICIENCY OF Mangifera indica MEDIATED ZINC OXIDE NANOPARTICLES - ALMANTO MAMURU, SOLOMON; UMAR HAROON, AISHA; HAMMAN BARAU, SAMINU (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2022)
The synthesis of metal nanoparticles using biological entities proven to be environmentally friendly against the physical and chemical method, the use of these metal nanoparticles as catalyst in the treatment of wastewater have also shown a lot of advantage against other techniques. In this research zinc oxide nanoparticles were successfully synthesized using aqueous leave extract of Mangifera indica, through a one-step synthesis protocol, results obtained from the UV-visible spectroscopy shows that the nanoparticles absorb light at 297 nm, while the scanning electron microscope reveals the morphology of the particles as flat sheet and highly agglomerated having 51.53 nm as the size from the X-ray diffraction. The FTIR spectroscopy reveals functional group of alcohol, amides, alkane, alkanes, amines, ethers Ar-O-R, alkenes, alkanes, as possible groups that may be responsible for the reduction of metal salt to metal oxide nanoparticles. The photocatalytic performance of the nanoparticles in the degradation of Congo red dye increases with increase in catalyst loading with the apparent kinetic rate constant, kapp as 8.8 x 10-2 min-1, 6.6 x 10-2 min-1, and 5.7 x 10-2 min-1 for 1 mg, 2 mg and 3 mg, respectively, suggesting that the nanoparticle has potential in the degradation of Congo red dye.